(3JfhjQ HUGFQ GdebdOjf aj efGbH GdCFeI GdeLJgOjfs - (3eQYj Hf jhSa Hf CHj HcQ Hf CMeO GdcQej GdebOSj GdMfHdi,J (B1033 (3g` s
(3ChdgG (B:s
(3CeG HYO Ef TGA Gddg JYGdi bO ChLO gPG GdYGde EjLGOkG LejdG hNU GdCfHjGA HeRjO GdaVd hLYd GdYdeGA dge hGQKjf dG SjeG GdCFeI GdeLJgOjf hbO Ufa GdCFeI ai aVGFdge cJHkG LeI EdG Cf efge eGgh GdehLR GdeNd s
(3BNQgG (B:s
(3bGd eDdag (B: (3aQZJ ef LeY gPg GdahGFO SfI KdGK hYTQjf HYO GdCda hGdMeO ddg QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B127 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(329 (3c(B) s
Keywords: (3GdJGQjNs